TGF-β activity protects against inflammatory aortic aneurysm progression and complications in angiotensin II–infused mice - Wang, Yu; Ait-Oufella, Hafid; Herbin, Olivier; Bonnin, Philippe; Ramkhelawon, Bhama; Taleb, Soraya; Huang, Jin; Offenstadt, Georges; Combadière, Christophe; Rénia, Laurent; Johnson, Jason L.; Tharaux, Pierre-Louis; et al. (The Journal of clinical investigation, 2010)
Complicated abdominal aortic aneurysm (AAA) is a major cause of mortality in elderly men. Ang II-dependent TGF-beta activity promotes aortic aneurysm progression in experimental Marfan syndrome. However, the role of TGF-beta in experimental models of AAA has not been comprehensively assessed. Here, we show that systemic neutralization of TGF-beta activity breaks the resistance of normocholesterolemic C57BL/6 mice to Ang II-induced AAA formation and markedly increases their susceptibility to the disease. These aneurysms displayed a large spectrum of complications on echography, including fissuration, double channel formation, and rupture, leading to death from aneurysm complications. The disease was refractory to inhibition of IFN-gamma, IL-4, IL-6, or TNF-alpha signaling. Genetic deletion of T and B cells or inhibition of the CX3CR1 pathway resulted in partial protection. Interestingly, neutralization of TGF-beta activity enhanced monocyte invasiveness, and monocyte depletion markedly inhibited aneurysm progression and complications. Finally, TGF-beta neutralization increased MMP-12 activity, and MMP-12 deficiency prevented aneurysm rupture. These results clearly identify a critical role for TGF-beta in the taming of the innate immune response and the preservation of vessel integrity in C57BL/6 mice, which contrasts with its reported pathogenic role in Marfan syndrome.